2015
DOI: 10.1007/s11010-015-2513-0
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II down-regulates natriuretic peptide receptor-A expression and guanylyl cyclase activity in H9c2 (2-1) cardiac myoblast cells: Role of ROS and NF-κB

Abstract: Atrial natriuretic peptide (ANP)/natriuretic peptide receptor-A (NPR-A) system is suggested as an endogenous anti-hypertrophic protective mechanism of the heart. We have shown previously that Angiotensin II (ANG II), an effector molecule of renin-angiotensin-aldosterone system, down-regulates NPR-A expression and its activity in vivo rat heart. However, the underlying mechanism by which ANG II down-regulates NPR-A expression in the heart is not well understood. Hence, the present investigation was aimed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Given the counter-regulatory actions between the RAAS and NPS, it is tempting to speculate that some RAAS components may serve as negative modulators of the NP receptors. Indeed, based on previous reports exploring ANGII effects on the NPS at multiple levels (32,33,(60)(61)(62)(63), ANGII may serve as a negative modulator of GC-A peptides from a drug . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the counter-regulatory actions between the RAAS and NPS, it is tempting to speculate that some RAAS components may serve as negative modulators of the NP receptors. Indeed, based on previous reports exploring ANGII effects on the NPS at multiple levels (32,33,(60)(61)(62)(63), ANGII may serve as a negative modulator of GC-A peptides from a drug . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the influence of ANGII on GC-A can be multi-dimensional and beyond the regulation of GC-A functional activity. For instance, ANGII has also been recently reported to affect GC-A expression at mRNA and protein levels (62,63,69). Whether and how these mechanisms may also be involved in the crosstalk between ANGII/AT 1 and GC-A deserve additional studies and emphasis especially in different disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying the link between increased PASP and thoracic empyema is unknown, our findings suggest that increased PASP could be a potential marker of disease activity and a predictor of prognosis in adult patients with thoracic empyema who undergo surgical treatment. Numerous studies have shown that inflammatory cytokines and stress are linked to hemodynamic and structural abnormalities in decompensated right ventricular failure, which is related to the activity of angiotensin II, natriuretic peptides, and reactive oxygen species [ 27 , 28 ]. Angiotensin II can influence calcium homeostasis and the production of cytokines such as tumor necrosis factor-α, interleukin-1, and interleukin-6 [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic interventions in left ventricular hypertrophy requires the lower circulatory levels of both ANP and BNP [54]. Thus, plants having potentially angiotensin converting enzyme inhibitory effect also plays an important role in the regulation of cardiac natriuretic peptide receptor-A via downregulating it and presenting cardioprotective effects [55]. Moreover, chlorogenic acid ang gallic acid present in Aa.Cr are direct inhibitor of circulatory Ag II, consequently decreasing ANP and BNP levels [28,51].…”
Section: Discussionmentioning
confidence: 99%